Hydrokinetic pancreatic function and insulin secretion are moduled by Cl− uniporter Slc26a9 in mice. (15th October 2021) - Li, T.; di Stefano, G.; Raza, G. S.; Sommerer, I.; Riederer, B.; Römermann, D.; Tan, X.; Tan, Q.; Pallagi, P.; Hollenbach, M.; Herzig, K.‐H.; Seidler, U.
Abstract: Aim: Slc26a9 is a member of the Slc26 multifunctional anion transporter family. Polymorphisms in Slc26a9 are associated with an increased incidence of meconium ileus and diabetes in cystic fibrosis patients. We investigated the expression of Slc26a9 in the murine pancreatic ducts, islets and parenchyma, and elucidated its role in pancreatic ductal electrolyte and fluid secretion and endocrine function. Methods: Pancreatic Slc26a9 and CFTR mRNA expression, fluid and bicarbonate secretion were assessed in slc26a9 −/− mice and their age‐ and sex‐matched wild‐type (wt) littermates. Glucose and insulin tolerance tests were performed. Results: Compared with stomach, the mRNA expression of Slc26a9 was low in pancreatic parenchyma, 20‐fold higher in microdissected pancreatic ducts than parenchyma, and very low in islets. CFTR mRNA was ~10 fold higher than Slc26a9 mRNA expression in each pancreatic cell type. Significantly reduced pancreatic fluid secretory rates and impaired glucose tolerance were observed in female slc26a9 −/− mice, whereas alterations in male mice did not reach statistical significance. No significant difference was observed in peripheral insulin resistance in slc26a9 −/− compared to sex‐ and aged‐matched wt controls. In contrast, isolated slc26a9 −/− islets in short term culture displayed no difference in insulin content, but a significantly reduced glucose‐stimulated insulin secretion compared to age‐ and sex‐matched wt islets, suggesting that the impaired glucose tolerance in the absence of Slc26a9 expression these is a pancreatic defect. Conclusions: Deletion of Slc26a9 is associated with a reduction in pancreatic fluid secretion and impaired glucose tolerance in female mice. The results underline the importance of Slc26a9 in pancreatic physiology.